COUNTRY AND CITY: TOURISM AS A SOCIO-SPATIAL EXPRESSION OF A HYBRID RELATIONSHIP IN STATES OF PARAÍBA AND RIO DE JANEIRO, BRAZIL / CAMPO E CIDADE: O TURISMO COMO EXPRESSÃO SOCIOESPACIAL DESSA RELAÇÃO HÍBRIDA NA PARAÍBA E NO RIO DE JANEIRO - Araújo, José Silvan Borborema; Marafon, Glaucio José (Geo UERJ, 2017)
doi: 10.12957/geouerj.2017.29939 The idea of country and city as antagonistic spaces that gradually grow distant from each other and that are doomed to be separated has lost validity regarding the spatial dynamics itself. This latter’s essence is in the reconstruction of histories and spaces through individual and collective actions, which shape objects and ascribe them with new roles in a continuous process of renewal. Aiming to analyze the hybrid relationship between city and country spaces in Paraíba and Rio de Janeiro — states of Brazilian northeast and southeast, respectively —, this study has considered tourist activities related to the production and reproduction of these spaces. It focuses mainly on the country, where traditional rural functions such as producing food for the city and providing workforce and raw material, share space with non-farming activities such as industry production and tourism services due to the spread of leisure areas in the rural space. This growth of non-farming activities results from technological developments represented by improvements and expansion of communication devices (telephony) and structures (roads and transportation). It contributes to the emergence of relations between the city and the country. Among socio-spatial and cultural changes in the country, tourism appears as a national way of valuing the rural space and its characteristics that reproduce a country and country life subjected to forces of nature, although technical elements typical of contemporary urban life such as infrastructure and communication had been already absorbed by the countryside. This article presents a geographical and critical treatment of the relationship between the country and the city relatively to tourism based on scientific works (academic articles, dissertations, and theses). Its sources include documents of agencies responsible for tourist activities in Paraíba and Rio de Janeiro as well as observations in loco. It analyzes such hybrid relationship to try to unravel how it is inscribed in each state territory and how touristic activity helps developing and maintaining rural activities in Paraíba and Rio de Janeiro country.